Bunga Cempaka Sebagai Elemen Estetik Pada Guci Ekspresi - Diajeng Wardani; Ni Made Rai Sunarini; I Ketut Muka (Pusat Penerbitan LP2MPP ISI Denpasar, 2023)
Jars are one of the crafts that come from clay. Guci itself has various uses, one of which is for expression in works. These expression jars help in conveying the ideas of ceramic artists. Indonesia itself has a variety of flowers, one of which is the champaca flower. Champaca flower has a characteristic that is quite striking. Besides having a beautiful shape, champaca flowers also have a very distinctive fragrance. The existence of this champaca flower is poured into the form of an expression jar with various views. The expression jars that are embodied have different meanings. The use of chrysolite flowers as an element in the creation of jars of expression goes through the stages of finding references, maturing ideas, and realizing works. The process of creating works using rotary techniques, slab techniques and also twist techniques. The creation of his work produces several works with images of expression that are in accordance with the initial concept of the author. There are several things that make this work unique, namely the results of the first and second burning which make it even more impressive. The resulting jar has a different appeal in each shape. The four works produced are an expression of the choice of champaca flower ideas as an aesthetic element. Keywords: Aesthetic Elemen, Champaca Flower, Expression Jars.